Penerapan Model Pembelajaran Problem Based Learning untuk Meningkatkan Hasil Belajar Siswa Kelas IV Sekolah Dasar - Jenysa Al Muslimah; Ms. Habiburahman; Endang Purwanti (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
This research was motivated by the low learning outcomes of class IV students at SD Negeri Bulakrejo 03 Sukoharjo on the learning content of Pancasila Education with material on the application of Pancasila in social life. The aim of this research is to find out the results of improving learning outcomes by implementing the PBL (Problem Based Learning) learning model in elementary schools. The subjects of this research were fourth grade students at SD Negeri Bulakrejo 03 Sukoharjo with a total of 30 students. This research uses classroom action research procedures consisting of planning, implementation, observation and reflection stages. Data collection techniques in this research used observation, tests and documentation. The criteria for assessing success in this material are 70 from 1-100 points in accordance with the criteria for completing the minimum PPKn lesson content. The research results show that the application of the PBL (Problem Based Learning) learning model can improve PPKn learning outcomes. At the pre-cycle stage the average student score was 65.25; in cycle I with a value of 75,60; and in cycle II it increased to 81.93. The use of the PBL (Problem Based Learning) learning model has been proven to improve student learning outcomes.